NILAI-NILAI SPIRITUALITAS SANTO TARSISIUS DALAM TUGAS PELAYANAN SEBAGAI MISDINAR DI PAROKI SANTO YOHANES PENGINJIL MANDALA - Sitepu, Abdi Guna; Nainggolan, Mika Gregorius; Simbolon, Erikson (Bahasa Indonesia, 2025)
This study aims to understand the spiritual values of Saint Tarcisius and the spiritual values of altar servers in the Saint John the Evangelist Mandala Parish. Altar servers are Catholic teenagers who demonstrate high dedication in serving the Church and assisting priests during the Eucharistic Celebration without expecting any reward. The spiritual values held by the altar servers include serving with love and selflessness, humility, and being responsible for the entrusted tasks. This study employs a qualitative approach. The research location is in the Saint John the Evangelist Mandala Parish. Data were collected through observation, interviews, and documentation. The data collected from the field will be analyzed by reducing, displaying, and triangulating the data using both techniques and sources. The data collection technique used is snowball sampling. The informants in the study consist of 10 people: 7 altar servers, 2 altar server supervisors, and 1 parish priest. The results of the study show that altar servers embody the spiritual values of Saint Tarcisius and their own spiritual values in their service duties.